The effect of N-methyl-D-aspartate receptor antagonists on the mismatch negativity of event-related potentials and its regulatory factors: A systematic review and meta-analysis - Guo, Xin; Yu, Jieyang; Quan, Chunhua; Xiao, Jinyu; Wang, Jiangtao; Zhang, Bo; Hao, Xiaosheng; Wu, Xuemei; Liang, Jianmin (Journal of psychiatric research, 2024)
This study investigates the influence of N-methyl-D-aspartate receptor (NMDAR) antagonists on the mismatch negativity (MMN) components of event-related potentials (ERPs) in healthy subjects and explores whether NMDAR antagonists have different effects on MMN components under different types of antagonists, drug dosages, and deviant stimuli. We conducted a comprehensive literature search of PubMed, EMBASE, and the Cochrane Library from inception to August 1, 2023 for studies comparing the MMN components between the NMDAR antagonist intervention group and the control group (or baseline). All statistical analyses were performed using Stata version 12.0 software. Sixteen articles were included in the systematic review: 13 articles were included in the meta-analysis of MMN amplitudes, and seven articles were included in the meta-analysis of MMN latencies. The pooled analysis showed that NMDAR antagonists reduced MMN amplitudes [SMD (95% CI) = 0.32 (0.16, 0.47), P < 0.01, I2 = 47.3%, p < 0.01] and prolonged MMN latencies [SMD (95% CI) = 0.31 (0.13, 0.49), P = 0.16, I2 = 28.3%, p < 0.01]. The type of antagonist drug regulates the effect of NMDAR antagonists on MMN amplitudes. Different antagonists, doses of antagonists, and types of deviant stimuli can also have different effects on MMN. These findings indicate a correlation between NMDAR and MMN, which may provide a foundation for the application of ERP-MMN in the early identification of NMDAR encephalitis.